The Consistency Of Islamic Corporate Financial Sustainability In Covid-19 Pandemic: An Empirical Analysis - Tita Nurvita; Yanuar Trisnowati; Rini Dwiyani Hadiwidjaja (AKRUAL: JURNAL AKUNTANSI, 2021)
The concept of sustainability is the ability of a company to carry out work program activities in a sustainable manner to achieve company goals. This study aims to examine empirically the consistency of financial sustainability in Islamic companies before and during the Covid-19 pandemic. To measure the financial sustainability performance, this study used ratios from financial income and financial expenditure. The sample in this study used purposive sampling that is 14 Islamic companies on the Indonesia Stock Exchange. Multiple linear regression and a chow test were used to examine the consistency. The result showed that The financial sustainability ratio of companies at the time of the pandemic has a higher value than before the pandemic. the pandemic period in Indonesia affected the financial stability of companies listed on the Jakarta Islamic Index. The independent variable that affects the dependent variable experiences structural changes in Indonesia in the period 2019 to quarter II of 2020